2012
DOI: 10.1017/s0144686x12000645
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and subjective wellbeing among older Europeans: does age make a difference?

Abstract: This inquiry examined whether social networks are associated with wellbeing among older-old people in the same way that they are among younger-old persons. The study focused on family respondents, aged  and older, from the second wave of the Survey of Health, Ageing and Retirement in Europe (N = ,). The statistical analysis regressed two wellbeing measures (the CASP quality of life scale and life satisfaction) on a range of social network variables from three domains: family structure and interaction, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 47 publications
(51 reference statements)
8
64
1
5
Order By: Relevance
“…These situations are often stressful for those involved, and can provide a sense of dependence, reduce self-esteem and consequently have a negative effect on QoL 19,21 . But the effect of the family structure on QoL may vary depending on the age group of the elderly person and other individual factors 22 .…”
Section: Discussionmentioning
confidence: 99%
“…These situations are often stressful for those involved, and can provide a sense of dependence, reduce self-esteem and consequently have a negative effect on QoL 19,21 . But the effect of the family structure on QoL may vary depending on the age group of the elderly person and other individual factors 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In support of these theoretical notions, research has consistently shown age-related changes and differences in social networks (Broese van Groenou, Hoogendijk, & van Tilburg, 2013;Cornwell, Schumm, Laumann, Kim, & Kim, 2014;van Tilburg, 1998;Wrzus, Hänel, Wagner, & Neyer, 2013), as well as age-dependent effects of social networks on wellbeing (Litwin & Stoeckel, 2013). Yet, although kin networks tend to be stable over the life span, significant changes have been observed primarily in the non-kin network, with an estimated reduction of one person per decade starting at the age of 60-65 years (Wrzus et al, 2013).…”
Section: Different Types Of Social Networkmentioning
confidence: 95%
“…High contact frequencies have been commonly associated with higher levels of QOL or other indicators of well-being in North America and European countries 21,29,[38][39][40][41] . However, some studies have associated frequency of contact with lower wellbeing 42 or have concluded that there is no association between contact frequency and the QOL/well-being of the elderly 7,31,43,44 .…”
Section: Type Of Relationship and Qol/well-beingmentioning
confidence: 99%